Clinical profile and colonoscopic findings in patients with lower gastrointestinal haemorrhage: a descriptive cross-sectional study - Bhattarai, Subash; Acharya, Ramesh Raj; Jwarchan, Bishnu; Karki, Dipesh (Asian Journal of Medical Sciences, 2020)
Background: Most of the bleeding in the lower gastrointestinal tract are usually located in the rectum, colon and terminal ileum. Colonoscopy is an invasive procedure used for both diagnostic and therapeutic purposes for detection of lower gastrointestinal (GI) tract pathologies and haemorrhage. Aims and Objective: The purpose of the study was to understand the clinical profile and colonoscopic findings in patients with lower gastrointestinal haemorrhage. Materials and Methods: Seventy-two patients presenting with lower GI haemorrhage were included in the study. All patients underwent colonoscopy after achieving hemodynamic stability and bowel preparation. Clinical profile and colonoscopic findings were studied. Results: The common aetiologies of lower GI haemorrhage were haemorrhoids followed by nonspecific colitis, colorectal polyp and carcinoma of colon. Rectum followed by sigmoid harbored majority of pathologies that presented with lower GI haemorrhage. Conclusions: The diagnosis of the pathological lesion and management of underlying cause not only prevents another episode of lower GI haemorrhage but also help in reducing morbidity and mortality. Colonoscopy or at least sigmoidoscopy is strongly recommended for evaluation, diagnosis and management of lower GI haemorrhage.